As Nuances de Brontë: o romance de formação e a tessitura da identidade de Jane Eyre - Kurtz, Karina Moraes (2020)
This dissertation explores the historical context that permeates Charlotte Brontë’s novel Jane Eyre. Puritanism and religious moralism that divide the thinking of the main character, Jane, thus marks the religious guilt to which English society was subjected. The dissertation explores female sexual repression in the Victorian era, how the protagonist's identity formation occurs in a hostile environment, and how Brontë's novel is also a narrative of resistance. Other points were: the similarity between Rochester and Jane, both suffer from the moral and religious judgment of the period from childhood to adulthood. Jane's resistance to the cruelties and oppressions she suffers throughout her life under the authoritarian and misogynistic regime of the nineteenth-century English educational system. Among other prime factors for understanding the oscillation between intuition and the ethical concepts that underly Jane's formation is the concept of bildungsroman or novel of education. Regarding the main theoretical texts is important to mention authors such as Virginia Woolf, Simone de Beauvoir, Eric Landowski, Zymunt Bauman, Stuart Hall, among others. This analysis takes into account the importance of works that show forms of resistance to oppressive and authoritarian regimes not only in relation to women, but in relation to men as well, bearing in mind that suffering and barbarism are not analogous only to one gender or ethnicity, but to all human beings, regardless of color, gender or social class. The analysis seeks to show that in times of fear and authoritarian regimes, literature becomes an inexhaustible source of denunciation against ideologies imposed as a form of social control, and offers the greatest wealth that human beings can possess:knowledge.